Tinjauan Yuridis Atas Keadilan Dalam Pemberian Upah Bagi Peserta Magang Berdasarkan Peraturan-Peraturan Ketenagakerjaan di Indonesia - Safitri, Adhesya Hani; Putri, Ambar Krisna; Rahmadani, Ardita Esti; Lestari, Dhea Indah; Larisa, Dita Mala Racel; Zahra, Humaerotuz; Halizhah, Nur; Putri, Ramona (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In this research, there is a formulation of the problem, which includes what are the rights and obligations of apprentices related to wages in accordance with applicable labour regulations, procedures for implementing labour regulations in ensuring fair wages for apprentices in Indonesia, and the impact of the practice of unpaid internships on legal protection and post-apprentice welfare in Indonesia. This study aims to be able to identify and analyse the rights and obligations of apprentices related to wages in accordance with applicable labour regulations, evaluate the implementation of labour regulations in ensuring fair wages for apprentices in Indonesia, and examine the impact of the practice of unpaid apprenticeship on the legal protection and welfare of apprentices in Indonesia. Normative juridical research is implemented to analyse and evaluate unpaid internship agreements and related legal aspects of legal protection for interns, besides that the approach used can be used to analyse internship agreements on existing legal rules in certain jurisdictions. In the analysis of this apprenticeship agreement, it is known that there are discrepancies when fulfilling facilities in the health of apprentices, providing pocket money, setting appropriate work time limits and appropriate job descriptions for apprentices. The legal protection is also still not in accordance with what has been in the internship agreement.